2018
DOI: 10.1121/1.5049584
|View full text |Cite
|
Sign up to set email alerts
|

The role of envelope periodicity in the perception of masked speech with simulated and real cochlear implants

Abstract: In normal hearing, complex tones with pitch-related periodic envelope modulations are far less effective maskers of speech than aperiodic noise. Here, it is shown that this is diminished in noise-vocoder simulations of cochlear implants (CIs) and further reduced with real CIs. Nevertheless, both listener groups still benefitted significantly from masker periodicity, despite the lack of salient spectral pitch cues. The main reason for the smaller effect observed in CI users is thought to be an even stronger cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…For the CI ears, there was even a slight trend towards greater activity in the left hemisphere. With current CI systems, the access to spectral information is severely limited, whereas temporal envelope modulations are conveyed fairly accurately ( Chatterjee and Peng, 2008 , Macherey and Carlyon, 2014 , Steinmetzger and Rosen, 2018 ). Models of auditory processing propose that the temporal resolution of the left auditory cortex is higher compared to the right one, which is in turn characterised by a greater spectral resolution ( Poeppel, 2003 , Zatorre et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the CI ears, there was even a slight trend towards greater activity in the left hemisphere. With current CI systems, the access to spectral information is severely limited, whereas temporal envelope modulations are conveyed fairly accurately ( Chatterjee and Peng, 2008 , Macherey and Carlyon, 2014 , Steinmetzger and Rosen, 2018 ). Models of auditory processing propose that the temporal resolution of the left auditory cortex is higher compared to the right one, which is in turn characterised by a greater spectral resolution ( Poeppel, 2003 , Zatorre et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few PET ( Giraud et al, 2001a , Giraud et al, 2001b , Giraud et al, 2000 , Mortensen et al, 2006 ) and fNIRS studies ( Chen et al, 2017a , Chen et al, 2017b , Mushtaq et al, 2020 , Olds et al, 2016 ) also used vowels or non-speech stimuli, systematic comparisons of basic auditory perception processes in CI users and normal-hearing (NH) controls are lacking. This is particularly striking with regard to pitch perception, which is very limited when listening through a CI and a crucial factor underlying the difficulties CI users encounter when listening to speech and music, especially in background noise ( Green et al, 2004 , Oxenham, 2008 , Steinmetzger and Rosen, 2018 ). The only pitch cues available to CI users are the periodic fluctuations of the temporal envelope of the acoustic input and hence their ability to identify the voice pitch contours that constitute a major part of prosody is strongly reduced ( Chatterjee and Peng, 2008 , Everhardt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…8. These representations were generated by computing the envelope power, as implemented in the front end of the mr-sEPSM, for each combination of auditory and modulation filters, time-averaged over the entire set of stimulus materials in each condition (see also Steinmetzger and Rosen, 2018). Figure 9, in contrast, shows modulation spectra of the eight different combinations of target speech and masker at each of the seven SNRs used for model prediction.…”
Section: Mr-sepsmmentioning
confidence: 99%
“…Since temporal-envelope coding is degraded by CS, a prime candidate for acoustic intervention is thus to modify the speech envelope which is essential for robust speech intelligibility (SI) [19][20][21][22][23][24][25][26][27]. Acoustic modifications of the speech-envelope shape and periodicity can improve SI [17,[28][29][30][31][32], especially in connection with hearing through cochlear implants [33][34][35][36][37][38]. Here, we go beyond these conventional approaches to develop a model-based type of auditory envelope processing that operates directly on the signal waveform to counteract the functional consequences associated with CS.…”
Section: Introductionmentioning
confidence: 99%
“…Since temporal-envelope coding is degraded by CS, a prime candidate for acoustic intervention is thus to modify the speech envelope which is essential for robust speech intelligibility (SI) [23][24][25][26][27][28][29][30][31]. Acoustic modifications of the speech-envelope shape and periodicity can improve SI [18,[32][33][34][35][36][37], especially in connection with hearing through cochlear implants [38][39][40][41][42][43]. Several studies have shown that envelope enhancement can be beneficial for speech recognition in individuals with temporal processing deficits [22,36,[44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%